PENGARUH PROBLEM-BASED LEARNING â€œWHATâ€™S ANOTHER WAY DAN DISCOVERY LEARNING DALAM MENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP - Jayanti Putri Purwaningrum (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
The aim of this study is to investigate the enhancement of the studentsâ€™ mathematical creative thinking ability in two classes whereby in one class, the students learning through problem-basedlearning â€œwhatâ€™s another wayâ€ and in another class, the students learning through discovery learning. The population of the study were all seven grade students in a junior high schools in Pekalongan regency. The sampling technique used purposive sampling and involved two classes as samples. The data were gathered by employing three research instruments such as mathematics creative thinking ability test, teaching materials, and observation sheet. The results of the study indicated that there was no significance difference in the enchancement between student who recieved WAW and student who recieve discovery learing.Keywords: Problem-Based Learning â€œWhatâ€™s Another Wayâ€, Discovery Learning, and Mathematics Creative Thinking Ability